Functional adjustment and cyclic application of Fe–Mn bimetal composite for Sb(V) removal: Transformation of iron oxides forms and a stable regeneration method. (1st September 2020) - Yang, Kunlun; Li, Cheng; Wang, Xiaomin; Liu, Yuanli; Li, Yizhou; Zhou, Chuchen; Wang, Zheni; Zhou, Jiasheng; Cao, Zhen; Xu, Xinhua
Abstract: In this work, the surface properties, functional groups and stability of Fe–Mn bimetal composite (FMBC) was modified through sintering to improve the weaknesses of pristine FMBC, such as poor separation performance, high amount of dissolved Fe and Mn, and easy phase transformation. Characterization analysis indicated that 2-line ferrihydrite in sintered FMBC (SFMC) gradually transformed into hematite with the phase-transition temperature of 450 °C. With the increasing sintering temperature and time, the dehydroxylation reaction enhanced and gradually became irreversible, while the BET surface area and porosity of SFMC firstly increased and then decreased, resulting in the initial increase and then sharp decrease of the amount of exposed hydroxyl groups on SFMC. The sintering treatment greatly improved the separation performance and stability of SFMC. 350 °C and 2 h were determined as the optimal sintering conditions of SFMC in this study and the calculated maximum adsorption capacity of optimal SFMC reached up to 95 mg/g. Freundlich model and pseudo-second-order kinetics model can describe the Sb(V) adsorption data well. As compared to pristine FMBC, optimal SFMC presented larger BET surface area and porosity, better separation performance and stability, lower dissolved Fe and Mn amount, larger cyclic adsorption efficiency and enough ability for Sb(V) removal in real textile wastewater. Furthermore, the inner sphere complexation between Sb(OH)6 - and exposed hydroxyl groups played a key role in adsorption. Additionally, the NaCl + NaOH elution exhibited greater Sb(V) desorption performance and effectively retarded the phase transformation of SFMC than NaOH solution. Graphical abstract: Image 1 Highlights: Calcining process facilitate transformation of ferrihydrite in SFMC to hematite. The surface area and porosity of optimal SFMC was higher than pristine FMBC. Regeneration of SFMC by NaCl + NaOH effectively retarded the phase transformation. Optimal SFMC after sintering had better cyclic Sb(V) adsorption performance.